Open Innovation in Small and Medium Enterprises: A Review of the Literature - Daniel RUSU; Maria FRANGIEH (Communications of International Proceedings, 2020)
In recent years, studies on open innovation in small and medium-sized enterprises (SMEs) have seen a spectacular increase. However, even in this context, there is still no comprehensive analysis for this area of research. Through this study we will examine the current state of research in terms of open innovation in SMEs because we want to structure the empirical results and at the same time draw a future research agenda. To a large extent these studies are conducted in a European context, along with a number of studies in Korea and China, while in the North American context studies are rare. The overall innovation performance of SMEs is largely enhanced by open innovation (OI). Even in this context, the relevant models and theories of managers are not well established in the literature. As a matter of fact, it is essential to recognize the competitive advantage sources of the enterprise. When these resources are recognized, it becomes easier to draw a plan regarding goal attainment and competitive advantage realization. The company’s leader plays a major role in deciding whether to venture into an open innovation strategy or to play it safe by adhering to a traditional closed innovation strategy. Consequently, it is up to the leader to outline the elements that profoundly impact the firm’s innovation activity.
Keywords: Literature Review; Strategy; SMEs; Open Innovation (OI); Leadership